An Employee Performance, Innovation, and Organizational Culture in The Perspective of Islamic Work Ethics and Maqāṣid al-Sharī‘ah (Evidence from PT Perkebunan Nusantara IV Sei Mangkei SEZ (Special Economic Zone), Indonesia - Ridha Tri Handayani; Suhairi; Purnama Ramadani Silalahi (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose  –  This study aims to analyze the influence of innovation, organizational culture, and burnout on employee performance at PT Perkebunan Nusantara IV Sei Mangkei. In addition, this research examines employee performance through the perspective of Islamic Work Ethics and maqāṣid al-sharī‘ah, emphasizing values of amanah, ihsān, responsibility, and balance in work practices. Method –  This study employed a quantitative approach using a survey method. Data were collected from 121 employees of PT Perkebunan Nusantara IV Sei Mangkei through structured questionnaires. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS to assess the relationships among innovation, organizational culture, burnout, and employee performance. Result – The findings indicate that innovation and organizational culture have a positive and significant effect on employee performance, while burnout does not show a significant direct effect. From the perspective of Islamic Work Ethics, employee performance is understood not merely as a managerial or productivity outcome, but as the fulfillment of amanah and moral responsibility. These results align with the objectives of maqāṣid al-sharī‘ah, particularly the protection of wealth (ḥifẓ al-māl), the protection of life (ḥifẓ al-nafs), and the preservation of human dignity, where innovation and a supportive organizational culture contribute to sustainable performance and employee welfare. Implication – This study contributes to the literature on Islamic economic law by demonstrating that employee performance in a Special Economic Zone is not merely a managerial outcome, but also an ethical and legal expression shaped by Islamic Work Ethics and the objectives of maqāṣid al-sharī‘ah. By integrating Islamic Work Ethics and maqāṣid al-sharī‘ah, the findings support the development of organizational policies that promote justice, balance, and employee welfare while sustaining performance and organizational continuity